The SAGE handbook of tourism management theories, concepts and disciplinary approaches to tourism - Cooper, Chris; Volo, Serena; Gartner, William; Scott, Noel (SAGE Publications Ltd, 2018)
The SAGE Handbook of Tourism Management is a critical, state-of-the-art and authoritative review of tourism management, written by leading international thinkers and academics in the field. With a strong focus on theories, concepts and disciplinary approaches to tourism studies, the chapters in this volume are framed as critical synoptic pieces covering key developments, current issues and debates, and emerging trends and future considerations for the field. Part One: Researching Tourism Part Two: Social Analysis Part Three: Economic Analysis Part Four: Technological Analysis Part Five: Environmental Analysis Part Six: Political Analysis This handbook offers a fresh and definitive look at tourism management, making it an essential resource for academics, researchers and students
Keywords: Tourism -- Management; Management; Tourismus